Safe food : bacteria, biotechnology, and bioterrorism - Nestle, Marion (Berkeley, CA : University of California Press, 2003)
"Marion Nestle, author of the critically acclaimed Food Politics, argues that ensuring safe food involves more than washing hands or cooking food to higher temperatures. It involves politics. When it comes to food safety, billions of dollars are at stake, and industry, government, and consumers collide over issues of values, economics, and political power - and not always in the public interest." "She demonstrates how powerful food industries oppose safety regulations, deny accountability, and blame consumers when something goes wrong, and how century-old laws for ensuring food safety no longer protect our food supply. She draws on three examples: microbial contamination of meat and poultry, genetically modified ingredients in supermarket products, and newly emerging hazards - bioterrorism among them. If as she says, food safety is a matter of politics, then problems of food safety require political solutions. Ensuring safe food requires government and industry to act more in the public interest, and consumers to exert democratic rights as citizens to make sure that they do." "Accessible, informed, and even-handed, Safe Food is for anyone for cares how food is produced and wants to know more about the real issues underlying today's headlines. It should be of interest to everyone who eats and wants food to be safe - from general readers to students, farmers, scientists, and anyone connected with the food industry or government."--BOOK JACKET.
Introduction: Food Safety Is Political -- Pt. 1. Resisting Food Safety -- 1. The Politics of Foodborne Illness: Issues and Origins -- 2. Resisting Meat and Poultry Regulation, 1974-1994 -- 3. Attempting Control of Food Pathogens, 1994-2002 -- 4. Achieving Safe Food: Alternatives -- Pt. 2. Safety as a Surrogate: The Ironic Politics of Food Biotechnology -- 5. Peddling Dreams: Promises versus Reality -- 6. Risks and Benefits: Who Decides? -- 7. The Politics of Government Oversight -- 8. The Politics of Consumer Concern: Distrust, Dread, and Outrage -- Conclusion: The Future of Food Safety: Public Health versus Bioterrorism -- App. The Science of Plant Biotechnology.
Includeye índice.
Notas: p. 283-326.
Keywords: Alimentos -- medidas de seguridad; Alimentos -- Biotecnología; Bioterrorismo; Contaminación de alimentos; Bioterrorism -- prevention & control; Microbiología alimenticia -- estandares; Food, Genetically Modified; Legislation, Food -- organization & administration; Safety; Voedselveiligheid; Biotechnologie; Voedselvergiftiging; Overheidsbeleid